Development of a four-item physical activity index from information about subsistence living in rural African women: a descriptive, cross-sectional investigation - Lambert Estelle V; Alberts Marianne; Cook Ian (BMC, 2009)
Abstract Background We investigated the criterion validity of a physical activity index (PAI) derived from socio-demographic variables obtained from convenience samples of rural African women. Methods We used a sample (N = 206) from a larger dataset which surveyed adult rural Africans during 1997, and data collected during 2003/4 from 138 adult rural African women. A three-point PAI (low-, medium- and high-subsistence) was constructed from four socio-demographic questions related to electricity, cooking methods, water collection and availability of motorized transport. Criterion measures included measures of adiposity, blood biochemistry, resting blood pressure (RBP), physical fitness (VO2max) and single-plane accelerometry (ACC). Results Age, educational level and health status were not related to PAI level (p > 0.1). There was a significant negative, linear trend between the PAI level and adiposity level (p < 0.04), and fasting blood glucose concentration (p < 0.0001), while VO2max was positively related to PAI level (p = 0.0190). The PAI level was positively and linearly related to ACC output, namely counts.day-1 (p = 0.0044), steps.day-1 (p = 0.0265), min.day-1 of moderate-to-vigorous activity (p = 0.0040), and the percentage of subjects adhering to physical activity public health guidelines (p = 0.0157). Other criterion measures did not reach significance, but were in the expected direction (sedentary behaviour: p > 0.08, RBP: p > 0.07). Conclusion The PAI derived from a socio-demographic questionnaire is a valid instrument for broadly categorizing levels of physical activity for this specific population of rural African women. As the epidemiological transition progresses, validity will need to be re-established.